Processing Code-Switches in the Presence of Others: An ERP Study - Kaan, Edith; Kheder, Souad; Kreidler, Ann; Tomić, Aleksandra; Valdés Kroff, Jorge R. (Frontiers in Psychology, 2020)
Code-switching is highly socially constrained. For instance, code-switching is only felicitous when those present are fluent in both languages as well. This means that bilinguals need to dynamically adjust their language control and expectation of code-switching to the current social situation or context. The aim of the present EEG study was to investigate how and when language control in the comprehension of code-switches is affected by the assumed language knowledge of others in the context. Spanish-English bilinguals read sentences with and without code-switches together with another Spanish-English bilingual or with an English monolingual. Switches elicited an early fronto-central positivity. This effect was smaller overall when a bilingual was present at the start of the study. In addition, the late positive complex found for switches was smaller when a bilingual was present rather than a monolingual, but only for those participants who were sensitive to the other’s language knowledge in their off-line judgments. These findings suggest that the bilinguals in our study expected and activated both languages when initially paired with a bilingual and that they more easily accommodated code-switches, in the presence of a bilingual than in the presence of a monolingual. Our findings support the view that language control can be modulated by the perceived language knowledge of others present, and are compatible with a dynamic control model of bilingual language comprehension.